The gender income gap and the role of family formation revisited: A replication of Bobbitt-Zeher (2007) - Fabian Ochsenfeld (Journal for Labour Market Research, 2017)
This article reports the results of a replication of Bobbitt-Zeher's 2007 article 'The Gender Income Gap and the Role of Education'. Models that emulate the original specifications (by and large) reproduce the original results. However, models that adhere to Bobbitt-Zeher's theory concerning the gendered effect of family formation call into question her finding that 'values appear to matter only modestly, while family formation has virtually no effect on the income gap'. – – Dieser Beitrag berichtet die Ergebnisse einer Replikation von Bobbitt-Zehers 2007 erschienenem Aufsatz 'The Gender Income Gap and the Role of Education'. Modelle, welche die ursprünglichen Spezifikationen nachbilden, replizieren (im Großen und Ganzen) die ursprünglichen Ergebnisse. Modelle, die hingegen Bobbitt-Zehers theoretischen Ausführungen bezüglich dem geschlechtsspezifischen Effekt der Familiengründung folgen, ziehen jedoch ihren Befund in Zweifel, wonach 'Werten nur eine bescheidene Bedeutung zukommt, während die Familiengründung praktisch keinen Effekt auf die Einkommensungleichheit hat'.
Keywords: C00; J12; J16; J24; J29; J31; 330; Gender gap; Motherhood penalty; Horizontal sex segregation; Replication; Decomposition methods